2012
DOI: 10.5798/diclemedj.0921.2012.02.0120
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of percutaneous endoscopic gastrostomies

Abstract: ÖZET Amaç: Oral gıda alamayan, özellikle yoğun bakım ünitelerinde yatmakta olan hastalara enteral beslenme desteği sağlamak amacıyla minimal invaziv bir metod olan perkutan endoskopik gastrostomi (PEG) deneyimimizi sunmayı amaçladık. Gereç ve yöntem:Bu çalışmada kliniğimizde Ocak 2000 -Haziran 2010 tarihleri arasında en az 4 hafta süreyle oral beslenemeyeceği öngörülerek PEG yerleştirilen 700 olgu retrospektif olarak incelendi. Hasta kayıtları endikasyonlar, komplikasyonlar ve sonuçları açısından değerlendiril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…In the study concluded by Tekin et al [1] , wound infection was observed at a rate of 15%. Cakir et al [17] , wound site infection was observed in 7.1%. In our study, wound site infection was observed in 26.32% of patients with complications,and postoperative bleeding was observed in 15.79%.…”
Section: Discussionmentioning
confidence: 92%
“…In the study concluded by Tekin et al [1] , wound infection was observed at a rate of 15%. Cakir et al [17] , wound site infection was observed in 7.1%. In our study, wound site infection was observed in 26.32% of patients with complications,and postoperative bleeding was observed in 15.79%.…”
Section: Discussionmentioning
confidence: 92%
“…In the geriatric age group and in pa- tients susceptible to infection, abscess or peritonitis may develop rarely with mortality. In the study conducted by Çakır et al, [9] who applied prophylactic antibiotics before the procedure, the rate of peristomal wound infection was found to be 7.1%. In our study, 7 (6.4%) patients developed peristomal wound infection.…”
Section: Discussionmentioning
confidence: 98%
“…PEG uygulanan hastaların çoğunu nörolojik hasarı olan hastalar oluşturur. Murat Çakır ve arkadaşlarının yaptığı 700 hastadan oluşan bir çalışmada 600 hastanın (%85) nörolojik hastalığı olduğu bildirilmiştir [5]. Takunaga ve arkadaşlarının çalışmasında bu oran %75 olarak bulunmuştur [6].…”
Section: Discussionunclassified
“…PEG işlemi sonrası peristomal enfeksiyon sık görülen bir komplikasyon olup farklı çalışmalarda %5-25 oranında bildirilmektedir. İşlem öncesi proflaktik antibiyotik uygulanan Çakır ve arkadaşlarının yaptığı çalışmada bu oran %7,1 olarak bulunmuştur [5]. Çalışmamızda ise 5 hastada peristomal enfeksiyon gelişmiş olup oranı %4,4 idi.…”
Section: Bulgularunclassified